Canker and Die-back of Robinia pseudocacia Linn. - a New Emerging Disease in Himachal Pradesh - Sharma, I. M.; Bhardwaj, S. S. (Indian Forester, 2001)
Canker and die-back disease in Black locust (Robinia pseudocacia) was identified to be caused by two different strains of Fusarium oxysporum and its incidence ranged between 27- 35 per cent in different localities of district Kullu and Mandi in Himachal Pradesh. Detailed symptomatology and preliminary studies on epidemiology and control have been discussed.